leman, D PENERAPAN METODE TEOREMA BAYES UNTUK DIAGNOSA GANGGUAN ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) PADA ANAK - Dedi Leman (LKP Unity Academy, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) or in Indonesian called Attention Deficit and Hyperactivity Disorder is a psychiatric disorder that causes sufferers to have difficulty concentrating and have excessive activity or can't stay still compared to normal people. Many people are not yet aware that if a child's excessive behavior and low level of concentration could result in the child suffering from ADHD, Bayesian decision theory is a fundamental statistical approach in pattern recognition. This approach is based on quantifying the trade-offs between various classification decisions using the probability and costs involved. arising from these decisions. Bayes' theorem is a theory of probability conditions that calculates the probability of an event (hypothesis) which depends on other events (evidence). In this research, a web-based expert system was built with a knowledge base from 3 experts to make it easier for parents of children to diagnose possible symptoms. suffered by his son. The results of system testing on experts with an average percentage of 90% from 3 experts, show that the expert system that has been created is able to diagnose the type of ADHD behavior suffered by children along with the level of confidence in the diagnosis.